Importancia de la publicidad para captar clientes o comensales de los restaurantes de 2, 3 y 5 tenedores de la ciudad de Iquitos - Arevalo Perez, Ana Isabel (2023)
The thesis "Importance of advertising to attract customers or diners of the restaurants of 2, 3 and 5 forks of the city of Iquitos", has the purpose of identifying advertising in the design of menu-card dishes, discounts and offers to customers, identify the use of social networks and advertisements on web platforms. Methodologically, it is a quantitative, descriptive, longitudinal study with a sample of 42 surveys determined by the convenience of restaurants with 2, 3 and 5 forks. The questionnaire technique with 16 questions and 4 questions of general sociodemographic data was used. The results were: "of the design of the letter-menu", it is statistically significant to the affirmative answers, of the "discounts and offers to clients", statistically significant of negative answers, of the "use of Social Networks" statistically very significant the answers negative and the "Announcement on the platform", statistically very significant negative. The hypothesis is rejected because most are significant negative results, consequently restaurants need to use advertising with technology and the Internet.